Towards a Green Investment Policy Framework The Case of Low-Carbon, Climate-Resilient Infrastructure - Corfee-Morlot, Jan (OECD Publishing, 2012)
Achieving low-carbon, climate-resilient (LCR) development is a policy goal of many governments today, and investment in built-infrastructure - in the energy, transport, water and building sectors - is a central part of the challenge. In the face of growing infrastructure needs and fiscal constraints, such transformational change will require large-scale private sector engagement. However, there is little policy experience on how to integrate climate and other environmental policy goals into investment policy frameworks and infrastructure planning. While many studies focus on the role of environmental and climate change policies to support a transition to a low-carbon, climate-resilient (LCR) economy, this paper suggests that other factors play a critical role to achieve this transition.
Keywords: Environment